1994
DOI: 10.1038/clpt.1994.167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of diazepam metabolism by fluvoxamine: A pharmacokinetic study in normal volunteers

Abstract: The effect of fluvoxamine on the pharmacokinetics of diazepam and metabolically derived N-desmethyl-diazepam was investigated in eight healthy volunteers. Each subject received a single oral dose of diazepam (10 mg) in a control session and on the fourth day of a 16-day treatment with fluvoxamine maleate (100 to 150 mg daily). Compared with the control session, concurrent fluvoxamine intake was associated with increased mean peak plasma diazepam concentrations (from 108 to 143 ng/ml, geometric means, differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…These suggested that there is a large inter-individual difference in bioavailability of fluvoxamine. Many previous papers described the effect of fluvoxamine on the pharmacokinetics of other drugs, which were metabolized by CYP2C19, 8 CYP3A4, [26][27][28] and CYP1A2. 28,29 However, the specific isoenzymes involved in fluvoxamine metabolism have not been identified; nevertheless, in vitro and in vivo the drug potently inhibits the metabolism of substrates for CYP1A2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggested that there is a large inter-individual difference in bioavailability of fluvoxamine. Many previous papers described the effect of fluvoxamine on the pharmacokinetics of other drugs, which were metabolized by CYP2C19, 8 CYP3A4, [26][27][28] and CYP1A2. 28,29 However, the specific isoenzymes involved in fluvoxamine metabolism have not been identified; nevertheless, in vitro and in vivo the drug potently inhibits the metabolism of substrates for CYP1A2.…”
Section: Discussionmentioning
confidence: 99%
“…3 Increases in fluvoxamine plasma concentrations have been reported when it is prescribed in combination with clomipramine 5 and butyrophenone. 6 Several reports indicate that fluvoxamine increases the plasma concentration of concurrently administered tricyclic antidepressants, 7 benzodiazepines, 8 carbamazepine 9 and theophilline. 10 This suggests the possibility that other drugs may be involved in drug interactions when co-administered with fluvoxamine in clinical drug therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Omeprazole, inhibitor of CYP2C19, decreased the clearance of intravenous diazepam by 27% (Andersson et al, 1990), and fluvoxamine, an inhibitor of CYP1A2, CYP2C19, and CYP3A4, reduced the apparent oral clearance of diazepam by 65%, and the elimination half-life was increased from 51 to 118 h (Perucca et al, 1994). It is noteworthy that ciprofloxacin, an inhibitor of CYP1A2, and cimetidine, an inhibitor of CYP1A2 and CYP3A4, reduced diazepam clearance by 37 and 38%, respectively (Kamali et al, 1993), but the exact mechanism for this is unknown.…”
Section: Cytochrome P450-mediated Drug Interactions and Benzodiazepinesmentioning
confidence: 99%
“…A suitable candidate enzyme was sought to test the hypothesis that RK i values will be conserved for a single inhibitor among the family of P450 1 enzymes. There is some in vivo evidence that fluvoxamine also inhibits the clearance of a number of drugs metabolized by CYP2C19, such as mephenytoin, chloroguanide, and diazepam (Perucca et al, 1994a;Xu et al, 1996;Jeppesen et al, 1997). In the case of the fluvoxaminemephenytoin interaction, the 0-to 8-h urine S/R ratio of mephenytoin increased from 0.16 to 0.55 after 100 mg/day fluvoxamine treatment for 2 weeks (Xu et al, 1996).…”
mentioning
confidence: 99%
“…Fluvoxamine also inhibited the CYP2C19 catalyzed bioactivation of chloroguanide: the formation clearance of 4-chlorophenylbiguanide decreased from 97 to 11 ml/min in CYP2C19-extensive metabolizers treated with 100 mg/day fluvoxamine for 6 days (Jeppesen et al, 1997). Diazepam oral clearance decreased from 0.4 to 0.14 ml/min/kg after treatment with 100 to 150 mg/day fluvoxamine for 4 days (Perucca et al, 1994a). The extent of inhibition observed in vivo is underpredicted with the reported in vitro K i values of fluvoxamine toward CYP2C19 (0.087-0.69 M; Rasmussen et al, 1998;Olesen and Linnet, 2000), when they are used in conjunction with the unbound plasma concentration of fluvoxamine.…”
mentioning
confidence: 99%